Multipotent adult hippocampal progenitor cells maintained as neurospheres favor differentiation toward glial lineages - Oh, Jisun (2014)
Adult hippocampal progenitor cells (AHPCs) are generally maintained as a dispersed monolayer population of multipotent neural progenitors. To better understand cell-cell interactions among neural progenitors and their influences on cellular characteristics, we generated free-floating cellular aggregates, or neurospheres, from the adherent monolayer population of AHPCs. Results from in vitro analyses demonstrated that both populations of AHPCs were highly proliferative under maintenance conditions, but AHPCs formed in neurospheres favored differentiation along a glial lineage and displayed greater migrational activity, than the traditionally cultured AHPCs. To study the plasticity of AHPCs from both populations in vivo, we transplanted GFP-expressing AHPCs via intraocular injection into the developing rat eyes. Both AHPC populations were capable of surviving and integrating into the developing host central nervous system, but considerably more GFP-positive cells were observed in the retinas transplanted with neurosphere AHPCs, compared to adherent AHPCs. These results suggest that the culture configuration during maintenance for neural progenitor cells (NPCs) influences cell fate and motility in vitro as well as in vivo. Our findings have implication for understanding different cellular characteristics of NPCs according to distinct intercellular architectures and for developing cell-based therapeutic strategies using lineage-committed NPCs.